Experimental and Numerical Study of Hydrodynamic Characteristics of Gullies for Buildings - Lo, Der-Chang; Chang, Shyy; Liu, Hsin-Feng; Chen, Chao-Yan (Water (Basel), 2018)
The miniaturization of a gully for building drainage system is attempted by installing a streamlined bump in the discharge pipe to maintain the minimum water trap height of 50 mm. The hydrodynamic performances of the air–water flows with or without glass balls through the two types of four-entry gullies with beveled or vertical nozzle flows are experimentally and numerically studied. The images of air–water–solid flow, maximum flow rates, self-purification properties and sustainable water traps subject to static and dynamic loadings are experimentally detected. The predictions of Computational Fluid Dynamics (CFD) unravel the characteristic flow structures to assist the interpretation of experimental results. In this respect, the observed entrained air bubbles and clustered glass balls in each gully correspond favorably to the regions with negative static pressures and weak flow momentums as disclosed by the CFD predictions. The measured ratios between discharged and supplied glass balls are consistently higher for the gully with beveled nozzle flows. The less efficient transportation of glass balls out of the drum for the gully with downward nozzle flow is attributed to the larger pressure gradients with considerable air entrainments. The relaxations of the form and friction drags over the nozzle-tip region and the reductions of air entrainments are essential for upgrading the maximum flow rate and the self-purification performance of a miniaturized gully.